Islam and the concept of justice / Khalid Ismail - Ismail, Khalid (Universiti Teknologi MARA, Perlis, 2010)
One of the principles which underly the Islamic worldview is justice. Justice also is the real goal of religion. It was the mission of every prophet. It is the message of every scripture. Islam is a religion which is a complete way of life. Justice is supreme and clearly defined in Islam, it is clearly emphasized that the objective of the creation of the universe is primarily to uphold justice and remove cruelty and evil. In this short paper the author shall attempt to elaborate the concept of justice and try to analayse it from Islamic theologico-philosphical views and not intended to discuss the topic mentioned above in various dimensions of discipline such as in politics, law and etceteras.